Muscular and kinematic features in speed skaters indicate a task-specific dystonia - Nijenhuis, B.; Tijssen, M. A. J.; van Zutphen, T.; Elting, J. W.; Schalkwijk, A. H. P.; Otten, E.; van der Eb, J. (Clinical Neurophysiology, 2023)
Objective Skater`s cramp is a movement disorder in speed skaters. We investigated whether affected skaters matched the disease profile of task-specific dystonia, specifically whether there was evidence of maladaptive muscle activity occurring simultaneously with aberrant movements (jerking). We further examined different skating intensities, positing no change would be more indicative of task-specific dystonia.